ANALYSIS OF HIT PHENOMENON BY THE FACTOR OF ADVERTISEMENT, WORD-OF-MOUTH, AND DECLINE OF AUDIENCES - Ahsanul Hafizhah, Tsamarah
The emergence of social media has facilitated interactions among people. Interactions on social media can be considered very similar to real-world interactions, allowing digital social media data to serve as a valuable resource for analyzing real-world dynamics. A hit phenomenon occurs when a particular topic experiences a surge in popularity, attracting a substantial number of followers within a certain time. This research aims to construct a mathematical model for the hit phenomenon, incorporating three main factors: advertisement, word-of-mouth, and the decline of audiences. The advertisement and word-of-mouth factors will impact the transition of potential hit followers to actual hit followers, while the decline of audiences factor will influence the transition of hit followers to former hit followers. The mathematical model of the hit phenomenon will review the dynamics of population growth among potential hit followers, hit followers, and former hit followers over a unit of time, thus the appropriate model form is a system of first-order differential equations. Then, a numerical simulation will be carried out on the model using the 4th-order Runge-Kutta method, with Google Trend data as the basis for implementing the simulation. This numerical simulation aims to derive conclusions regarding the three factors that influence the hit phenomenon model specifically focusing on widely used social media platforms by Indonesian people in the last 5 years, namely TikTok, Instagram, and X (Twitter). Analysis of the last 5 years reveals that the impact of advertising factors on the trend of X (Twitter) is slightly superior to Instagram, while TikTok trails behind these two social media platforms. Additionally, the influence of word-of-mouth on TikTok trends surpasses that on X (Twitter) and Instagram. Examining the influence of the decline of audiences on social media trends reveals that TikTok has the most significant impact, followed by Instagram, and X (Twitter) with the least influence. From all the numerical simulations carried out, it is observed that the decline of audiences factor holds considerable influence on the hit phenomenon.